Upaya Peningkatan Persepsi Diri Melalui Pelatihan Pengenalan Diri = Effort to Increase Self-Perception Through Self?Effort to Increase Self-Perception Through Self Understandin - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACTRecently, public attention has been focused on ways of developing Intelligence Quotient (IQ) and also emotional maturity. This is because one's success is not only determined by his IQ but also by his emotional maturity. A characteristic of one whose emotional maturity has developed when he possesses self-awareness so that he will be able to control his inner-drives. This research is intended to find out the influence of self-understanding training on the development of self-perception. It is also intended to find out whether there is a relationship between school and self-perception.The research is experimental correlational study,using self-understanding training and school achievement as its independent variables and self-perception as its dependent one. The subjects of the experiment are 20 fourth-grade pupils of the SDK Theresia, 9 to 10 years of age. Subjects were assigned randomly into experimental and control groups based on a pretest-posttest design. The data are analyzed using one- way anova. The subjects of the correlational study are 58 fourth-grade pupils of SDK Theresia, 9 to 10 years of age. The data are analyzed using product moment correlation.The results of the research showed: (1) there was a positive efffect of self-understanding training toward self-perception (2) There was no correlation between school achievement and self-perception.